Consumer Behaviour on The E-Commerce Market After the Introduction of The General Data Protection Regulation (GDPR) - Anna Rybak; Magdalena Roman (Communications of International Proceedings, 2022)
The research void regarding consumer behavior after the introduction of the GDPR became the research goal of our article. To this end, we conducted an analysis based on data from Eurobarometer, EU citizens were examined by age, socio-occupational status, and place of residence. The data analysis consisted of a statistical multivariate analysis of descriptive models using the k-means clustering. Our research shows that the introduction of the GDPR changed the attitude of EU citizens towards the protection of personal data. Primarily, e-consumers' interest in and knowledge of data protection have increased, as well as their fear of losing their personal data.  The paper also highlights the need for further research in this area.
Keywords: GDPR; „Brussels effect”; e-commerce market; protection od digital privacy